Optimalisasi Pemanfaatan Otomasi Greenhouse Dan Hydroponic Dalam Meningkatkan Produksi Dan Keberhasilan Terhadap Pertanian Budidaya Pakcoy Di PT Inamas Sintesis Teknologi - Yanti Grace Hutasoit; Yanda Bara Kusuma (Institut Nalanda, 2023)
This research aims to investigate the use of greenhouse and hydroponic automation in increasing the production and success of pakcoy cultivation. This study was conducted by adopting a case study approach at PT Inamas Sintesis Teknologi. The research methods used include field surveys, data collection through observation, interviews with farmers, and statistical data analysis. This study also analyzes the determinants of successful implementation of greenhouse and hydroponic automation and their impact on pakcoy cultivation. The results showed that the use of greenhouse and hydroponic automation significantly increased pakcoy production compared to conventional methods. This study provides an important contribution to the understanding of the importance of greenhouse and hydroponic automation in increasing the production and success of pakcoy cultivation. The results of this research can provide insight to farmers and stakeholders regarding the importance of investing in modern agricultural technology to increase the yield and efficiency of agricultural businesses.